2010
DOI: 10.1007/s00436-010-1886-y
|View full text |Cite
|
Sign up to set email alerts
|

Biological and immunological activity of new imidazolidines against adult worms of Schistosoma mansoni

Abstract: The only drug available for treating schistosomiasis is praziquantel, however there are already reports of resistance to its use in treatment, making it necessary to search and develop new compounds to combat schistosomiasis. We tested, in vitro, two new products, Laboratório de Planejamento de Síntese de Fármacos (LPSF)/5-(4-chloro-benzylidene-3-(4-nitrebenzyl)-4-thioxo-imidazolidin-2-one (RZS-2) and LPSF/5-(4-fluoride-benzylidene-3-(4-nitrebenzyl)-4-thioxo-imidazolidin-2-one (RZS-5) imidazolidines, against a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 31 publications
1
13
0
1
Order By: Relevance
“…Moreover, mefloquine was shown to exhibit a high capacity to induce morphological alteration in the outer membrane of schistosomula and adult schistosomes. Other examples of promising antischistosomal drugs under research include benzothiazole derivatives (Mahran et al 2007), aminoalkanethiols and corresponding disulfides (de Oliveira Penido et al 2008), alkoxyalkyl esters of acyclic nucleoside phosphonates (Botros et al 2009), trioxaquines (Boissier et al 2009), and thioxo-imidazoline compounds (Neves et al 2010(Neves et al , 2011. In addition, modifications in the manner of drug delivery for drugs with poor hydrosolubility have also been investigated to increase antischistosomal efficacy (de Araújo et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, mefloquine was shown to exhibit a high capacity to induce morphological alteration in the outer membrane of schistosomula and adult schistosomes. Other examples of promising antischistosomal drugs under research include benzothiazole derivatives (Mahran et al 2007), aminoalkanethiols and corresponding disulfides (de Oliveira Penido et al 2008), alkoxyalkyl esters of acyclic nucleoside phosphonates (Botros et al 2009), trioxaquines (Boissier et al 2009), and thioxo-imidazoline compounds (Neves et al 2010(Neves et al , 2011. In addition, modifications in the manner of drug delivery for drugs with poor hydrosolubility have also been investigated to increase antischistosomal efficacy (de Araújo et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…The production of NO may also contribute to worm mortality by way of S-nitrosylation of cysteine proteases, given that schistosomes express cysteine proteases that play a role in digestion, reproduction, and protein turnover and that this appears to be a common and widespread mechanism (58,62). Studies have also shown that compounds that induce the NO release possess potential immunomodulatory properties (63)(64)(65). The present study found that LpQM-14 stimulated NO production for the three incubation times analyzed, while LpQM-45 stimulated production only after 48 h of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…As previously noted, there was no structural alteration of the spines and tubercles on the surface of the parasites caused by incubation with LDL, compared with studies involving drugs administration such as praziquantel and artemether that cause swelling, erosion, peeling, vesiculation, and collapse of tegumental ridges (Shuhua et al 2002;Neves et al 2010). Long-term LDL incubations (120 min) caused a decrease of approximately 30% of the original particles' size in the beginning of the experiments.…”
Section: Discussionmentioning
confidence: 76%